KRAS-associated microRNAs in colorectal cancer - Hamizah Ibrahim; Ya Chee Lim (Frontiers Media S.A., 2020)
Colorectal cancer (CRC) is one of the leading causes of cancerrelated death worldwide. Despite progress in treatment of cancers, CRC with KRAS mutations are resistant towards anti-EGFR treatment. MicroRNAs have been discovered in an exponential manner within the last few years and have been known to exert either an onco-miRNA or tumor suppressive effect. Here, the various roles of microRNAs involved in the initiation and progression of KRAS-regulated CRC are summarized. A thorough understanding of the roles and functions of the plethora of microRNAs associated with KRAS in CRC will grant insights into the provision of other potential therapeutic targets as well as treatment. MicroRNAs may also serve as potential molecular classifier or early detection biomarkers for future treatment and diagnosis of CRC.